PENGGUNAAN MEDIA TEKNOLOGI PEMBELAJARAN UNTUK MENINGKATKAN MINAT BELAJAR SISWA SMA BATAM: The Use of Learning Technology Media to Increase the Learning Interest of Batam High School Student - Arsyad Sumantika; Ganda Sirait; Elva Susanti; Elsya P. L. Tarigan; Yunisa Oktavia (PUAN INDONESIA, 2023)
Learning media is a connecting medium between material content and students who become learning objects. In its implementation, the use of learning media that is less effective results in a decrease in student learning interest, therefore an effective method is needed. The community service team tries to provide training on how to make learning easier and more enjoyable. There are several trainings conducted, namely website training, office training, use of interactive language, and use of information technology. The object of this service activity is carried out at a high school in Batam. Based on the results of the activity, it can be concluded that through the use of more interactive technology-based learning media it can increase a higher interest in learning so that it can further maximize the potential possessed by students. The advice given is that there must be support from parents and teachers by providing adequate facilities and the need for supervision so that the learning process can run optimally.